The Influence of Aging Period, Freezing Temperature and Packaging Material on Frozen Beef Chemical Quality (Jurnal Ilmu dan Teknologi Hasil Ternak, 2008)
The objective of the study was to evaluate the influences of aging period, freezing temperature and packaging material on the frozen beef chemical quality. The material of the study was 2-3 years old Ongole grade beef of the Longissimus dorsi part,  and was then classified into 3 treatments, namely A (aging periode; 0, 12 and 24 hours), B (freezing temperature; -10°C and -20°C) and C (packaging material; aluminum foil (Al), polyprophylene (PP), polyethylene (PE) and without packaging material). The observed variables were water content, crude protein, fat, ash content. The data were analyzed by the Completely Randomized Design (CRD) in the Factorial (3x2x4) pattern. The results indicated that the aging periode decreased the water content, and ash content significantly (P<0.05), and decreased the crude protein but increased the fat content insignificantly. The lower freezing temperature prevented the decreases of the water content, and ash content significantly (P<0.05), but prevented the decrease of crude protein, fat content insignificantly. The packaging material could prevent the decreases of water content, ash content significantly (P<0.05), but prevent the decreases of protein, and fat content insignificantly. A significant interaction (P<0.05) occured between the freezing temperature and packaging material factors on ash content of the frozen beef. The conclusion was the frozen beef without aging has a high of water content, protein, and ash, but has a low fat content.Temperature at -200C and using aluminium foil packaging can prevent decreasing quality of frozen beef. Keywords : Aging period, freezing temperature,  packaging material